Peripheral nerve injury with Nexplanon removal: case report and review of the literature - Rachel Lefebvre; Marianne Hom; Hyuma Leland; Milan Stevanovic (BMC, 2018)
Abstract Background Implantable devices offer convenient, long-acting, and reversible contraception. Injury to the peripheral nerves and blood vessels have been reported as rare complications of implantation and extraction. Case presentation We present a case of ulnar nerve injury in a 21-year-old woman from attempted in-office removal of a deeply implanted Nexplanon® device. The injury resulted in an ulnar nerve palsy requiring surgical exploration, neuroma excision, and sural nerve cable grafting. Conclusions In-office attempts to remove contraceptive implants that are deep or have migrated can cause iatrogenic nerve injury. Devices that are non-palpable, deep, or migrated should be imaged before formal surgical exploration and removal. Any patient with neurologic symptoms after placement or after attempted removal requires prompt diagnosis and referral to a peripheral nerve surgeon.